The use of fiducial markers in image‐guided radiotherapy for gastric cancer. Issue 5 (13th October 2013) - Sia, Joseph; Glance, Simon; Chandran, Sujievvan; Vaughan, Rhys; Hamilton, Chris
Summary The use of fiducial markers (FM) in image‐guided radiotherapy (IGRT) to increase treatment precision is emerging for upper gastrointestinal malignancies. To our knowledge there is no data beyond technical reports for the use of FMs in IGRT for gastric cancers in the current literature. We report a case of an 89‐year old gentleman with localised gastric cancer who was deemed unfit for surgery and chemotherapy. He had FMs inserted endoscopically around the tumour via ultrasound guidance and received radiotherapy with a high‐dose palliative intent via a two‐phase technique to 54 Gy in 30 fractions with IGRT. The use of FMs allowed confidence in tumour delineation and together with IGRT enabled precise and safe delivery of a higher dose. The patient tolerated the treatment without significant toxicity and had no evidence of residual or recurrent tumour 12 months following radiotherapy. The use of FMs with IGRT in upper gastrointestinal malignancies warrants further collaborative studies.